Transcriptional Regulation of JARID1B/KDM5B Histone Demethylase by Ikaros, Histone Deacetylase 1 (HDAC1), and Casein Kinase 2 (CK2) in B-cell Acute Lymphoblastic Leukemia - Wang, Haijun (J Biol Chem, 2016)
Impaired function of the Ikaros (IKZF1) protein is associated with the development of high-risk B-cell precursor acute lymphoblastic leukemia (B-ALL). The mechanisms of Ikaros tumor suppressor activity in leukemia are unknown. Ikaros binds to the upstream regulatory elements of its target genes and regulates their transcription via chromatin remodeling. Here, we report that Ikaros represses transcription of the histone H3K4 demethylase, JARID1B (KDM5B). Transcriptional repression of JARID1B is associated with increased global levels of H3K4 trimethylation. Ikaros-mediated repression of JARID1B is dependent on the activity of the histone deacetylase, HDAC1, which binds to the upstream regulatory element of JARID1B in complex with Ikaros. In leukemia, JARID1B is overexpressed, and its inhibition results in cellular growth arrest. Ikaros-mediated repression of JARID1B in leukemia is impaired by pro-oncogenic casein kinase 2 (CK2). Inhibition of CK2 results in increased binding of the Ikaros-HDAC1 complex to the promoter of JARID1B, with increased formation of trimethylated histone H3 lysine 27 and decreased histone H3 Lys-9 acetylation. In cases of high-risk B-ALL that carry deletion of one Ikaros (IKZF1) allele, targeted inhibition of CK2 restores Ikaros binding to the JARID1B promoter and repression of JARID1B. In summary, the presented data suggest a mechanism through which Ikaros and HDAC1 regulate the epigenetic signature in leukemia: via regulation of JARID1B transcription. The presented data identify JARID1B as a novel therapeutic target in B-ALL and provide a rationale for the use of CK2 inhibitors in the treatment of high-risk B-ALL.